WEBINAR MUDAH MENULIS ARTIKEL PADA JURNAL NASIONAL UNTUK GURU, DOSEN DAN MAHASISWA - Suhardi, Muhamad (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity presented a webinar entitled "Easy Writing of Articles in National Journals for Teachers, Lecturers, and Students," aimed at improving scientific article writing competency among academics and aspiring academics. The phenomenon of the still low quantity and quality of scientific publications in Indonesia is the main background for implementing this activity. Many teachers, lecturers, and students face difficulties in understanding the systematics, writing rules, and publication strategies in national journals. Therefore, this webinar was designed as a practical solution to bridge this knowledge and skills gap, utilizing online platforms (Zoom Meeting and YouTube Live Streaming) to reach a wider participant reach. The activity implementation method involved several crucial stages. The preparation stage involved internal coordination of the implementing team through a WhatsApp group to ensure agenda alignment and task distribution. The webinar itself featured expert speakers who presented comprehensive material, starting from finding research ideas, scientific article systematics, compiling backgrounds, methods, results and discussions, conclusions, to tips for writing bibliographies, avoiding plagiarism, publication strategies, and understanding credit points. The webinar demonstrated a positive response and high enthusiasm from participants, as evidenced by the significant attendance from various institutions. The material presented was deemed highly relevant and applicable, helping participants understand the intricacies of scientific article writing, which is often a challenge. Participants also gained valuable insights into writing ethics and effective publication strategies. The conclusion of this activity was that the "Easy Writing of Articles in National Journals" webinar successfully improved participants' understanding and skills, contributing to increased scientific literacy and publication productivity in Indonesia. Future recommendations include continuing similar programs with a more specific scope or providing writing assistance to maximize their positive impact. ABSTRAK Kegiatan pengabdian masyarakat ini menyajikan webinar berjudul "Mudah Menulis Artikel pada Jurnal Nasional untuk Guru, Dosen, dan Mahasiswa", bertujuan untuk meningkatkan kompetensi penulisan artikel ilmiah di kalangan akademisi dan calon akademisi. Fenomena masih rendahnya kuantitas dan kualitas publikasi ilmiah di Indonesia menjadi latar belakang utama pelaksanaan kegiatan ini. Banyak guru, dosen, dan mahasiswa menghadapi kesulitan dalam memahami sistematika, kaidah penulisan, hingga strategi publikasi pada jurnal nasional. Oleh karena itu, webinar ini dirancang sebagai solusi praktis untuk menjembatani kesenjangan pengetahuan dan keterampilan tersebut, memanfaatkan platform daring (Zoom Meeting dan YouTube Live Streaming) untuk mencapai jangkauan peserta yang lebih luas. Metode pelaksanaan kegiatan mencakup beberapa tahap krusial. Tahap persiapan melibatkan koordinasi internal tim pelaksana melalui grup WhatsApp untuk memastikan keselarasan agenda dan pembagian tugas. Pelaksanaan webinar itu sendiri menampilkan narasumber ahli yang menyajikan materi komprehensif, dimulai dari menemukan ide penelitian, sistematika artikel ilmiah, menyusun latar belakang, metode, hasil dan pembahasan, kesimpulan, hingga tips menulis daftar pustaka, menghindari plagiat, strategi publikasi, dan pemahaman angka kredit. Hasil pelaksanaan webinar menunjukkan respons positif dan antusiasme tinggi dari peserta, yang dibuktikan dengan jumlah kehadiran signifikan dari berbagai institusi. Materi yang disajikan dinilai sangat relevan dan aplikatif, membantu peserta memahami seluk-beluk penulisan artikel ilmiah yang sering menjadi kendala. Peserta juga mendapatkan wawasan berharga mengenai etika penulisan dan strategi publikasi yang efektif. Kesimpulan dari kegiatan ini adalah bahwa webinar "Mudah Menulis Artikel pada Jurnal Nasional" berhasil meningkatkan pemahaman dan keterampilan peserta, berkontribusi pada peningkatan literasi ilmiah dan produktivitas publikasi di Indonesia. Rekomendasi ke depan adalah melanjutkan program serupa dengan cakupan yang lebih spesifik atau pendampingan penulisan untuk mengoptimalkan dampak positif.